PENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI PENGEMBANGAN FLIPBOOK INTERAKTIF - Anggita Bella Verbena; Arfi Salsafira Ayu Handiyarti; Arssiyah Ellam Umaeroh; Aviza Ayuni Wulan; Awwang Anggara Yoga; Bagus Nugraha Deby Ariyadi; Yeni Anistyasari; Ida Fitriyaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of using interactive flipbook media in improving student learning outcomes in Informatics subjects at the Vocational High School (SMK) level. The urgency of this research lies in the need for innovative learning media that can answer the challenges of the 21st century, especially in improving student learning outcomes that have been hampered by conventional approaches. This research uses the Systematic Literature Review (SLR) method by reviewing 10 relevant articles from 2019-2024. After going through the selection stage based on the inclusion and exclusion criteria, the ten most relevant articles were obtained for analysis. Data were analyzed using a categorization approach based on the validity of material experts, media experts, and students’ responses to the feasibility of teaching materials. The results showed that the average validity of material experts was 90.11%, the validity of media experts was 91.7%, and the feasibility of teaching materials was 89.6%, all of which were in the “very valid” category. These findings indicate that interactive flipbooks are very feasible and effective learning media in improving student learning outcomes. Interactive flipbooks not only present material visually and attractively, but also include interactive elements such as animations, videos, and quizzes that strengthen concept understanding. Thus, this study recommends the wider utilization of interactive flipbooks as a technology-based pedagogical solution in supporting active, innovative and meaningful learning.